Development of Renal Dosing Guidelines: A Prospective Study - Parvathagiri, Varun; Yerramilli, Aparna; Mudigonda, Somasekhar; Kethavath, Swathi; Yeravalli, Nikitha Rao; Peteti, Navya Teja (Indian Journal of Pharmacy Practice)
Background: Patients with Chronic Kidney Disease are at increased risk for potentially harmful prescribing. The selection of appropriate dosing for patients with Chronic Kidney Disease is important to avoid unwanted drug effects, maximize therapeutic efficacy and ensure optimal patient outcomes. Aim: To study the impact of renal dosing guidelines on prescribing pattern in patients with CKD. Methods: This was a prospective, interventional study conducted at a tertiary care centre. In the pre-interventional phase, the case sheets of all the in-patients with CKD with creatinine clearance of <50mL/min were collected and reviewed for the demographics, lab parameters and medications prescribed. The pre-intervention phase served as the control.As a part of intervention, pocket guides were prepared listing out the drug dosing in renal impairment and were distributed to all clinicians and the patient care areas. In the post-interventional phase, the drug charts were reviewed to observe any improvement in the dosing pattern of renally eliminated drugs. Results: In the pre-intervention study, drug dosing adjustment was needed in 246 drugs where 59 drugs (23%) were inappropriately dosed. In the post-intervention study, this number was significantly lowered to 23 (8%) drugs out of 284 drugs (p=0.0001) which needed renal dosing. Statistically significant improvements were seen with prescribing of antibiotics (p=0.0017), hypolipidemics (p=0.0449) and antiarrhythmic agents (p=0.0034). Conclusion: The dosing of majority of the renally eliminated drugs followed the recommendations of the package inserts. With the increasing awareness created by the pocket guides, there was a significant improvement in renal dosing. There is a need in health care settings to monitor the use of renally eliminated medications to reduce the adverse effects. The clinical pharmacists in collaboration with clinicians play a significant role in optimizing patient outcomes.
Keywords: Kidneys; Dose adjustment; Renal failure; Creatinine clearance; Medications